Mitigating Supply Chain Vulnerabilities in Nigeria - Akeem F. Olatunji; Ayoola A. Ayoola (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
This study investigates the role of insurance as a financial risk control strategy in mitigating supply chain vulnerabilities in Nigeria, a country characterized by significant infrastructural, political, and regulatory challenges. Employing a survey research design, the research integrates quantitative analysis of survey data from 366 respondents with insights from relevant literature. The survey utilized a 5-point Likert scale to assess perceptions of key supply chain vulnerabilities and the effectiveness of insurance in addressing these risks. Results reveal that the most significant supply chain vulnerabilities in Nigeria are regulatory uncertainty (mean = 3.21), political instability (mean = 3.19), and infrastructure inadequacies (mean = 3.13). These factors were ranked as the top concerns, reflecting their substantial impact on supply chain efficiency. In contrast, issues related to insurance, such as high premiums (mean = 3.00) and limited coverage options (mean = 3.08), were perceived as less significant. Regression analysis further elucidates the relationship between insurance effectiveness and supply chain vulnerability mitigation. The model shows a strong positive correlation (R = 0.78), with insurance effectiveness explaining 60.8% (R² = 0.608) of the variance in supply chain risk mitigation. The ANOVA results confirm the significance of the regression model (F = 90.00, p-value = 0.0000), indicating that insurance effectiveness significantly contributes to reducing supply chain vulnerabilities. The coefficient analysis reveals that for each unit increase in insurance effectiveness, there is a 0.70 increase in vulnerability mitigation, highlighting the substantial impact of effective insurance coverage.